Infliximab monitoring in Crohn’s disease: a neural network approach for evaluating disease activity and immunogenicity - Luis Eduardo Miani Gomes; Livia Moreira Genaro; Marina Moreira de Castro; Renato Lazarin Ricci; Livia Bitencourt Pascoal; Filipe Botto Crispim Silva; Pedro Henrique Leite Bonfitto; Michel Gardere Camargo; Ligiana Pires Corona; Maria de Lourdes Setsuko Ayrizono; Anibal Tavares de Azevedo; Raquel Franco Leal (Therapeutic Advances in Gastroenterology)
Background: The treatment for Crohn’s disease (CD) has increasingly required the use of biological agents. Safe and affordable tests have led to the active implementation of therapeutic drug monitoring (TDM) in clinical practice, which, although not yet widely available across all health services, has been proven effective. Objective: To analyze serum infliximab (IFX) and antidrug antibody (ADA) levels in CD patients, compare two tests, as well as construct a prediction of neural network using a combination of clinical, epidemiological, and laboratory variables. Design: Cross-sectional observational study. Method: A cross-sectional observational study was conducted on 75 CD patients in the maintenance phase of IFX treatment. The participants were allocated into two groups: CD in activity (CDA) and in remission (CDR). Disease activity was defined by endoscopic or radiological criteria. Serum IFX levels were measured by enzyme-linked immunosorbent assay (ELISA) and rapid lateral flow assay; ADA levels were measured by ELISA. A nonparametric test was used for statistical analysis; p value of ⩽0.05 was considered significant. Differences between ELISA and rapid lateral flow results within the measurement range were assessed by the Wilcoxon test, Passing–Bablok regression, and Bland–Altman method. Prediction models were created using four neural network sets. Neural networks and performance receiver operating characteristic curves were created using the Keras package in Python software. Results: Most participants exhibited supratherapeutic IFX levels (>7 mg/mL). Both tests showed no difference in IFX levels between the CDA and CDR groups ( p  > 0.05). The use of immunosuppressive therapy did not affect IFX levels ( p  > 0.05). Only 14.66% of patients had ADA levels >5 AU/mL, and all ADA-positive participants exhibited subtherapeutic IFX levels in both tests. The median results of both tests showed significant differences and moderate agreement ( r  = −0.6758, p  < 0.001). Of the four neural networks developed, two showed excellent performance, with area under the curve (AUCs) of 82–92% and 100%. Conclusion: Most participants exhibited supratherapeutic IFX levels, with no significant serum level difference between the groups. There was moderate agreement between tests. Two neural network sets showed disease activity and the presence of ADA, noninvasively determined in patients using IFX by presenting an AUC of >80%.